Continuous QoS-compliant Orchestration in the Cloud-Edge Continuum. - Bisicchia, Giuseppe; Forti, Stefano; Pimentel-Sánchez, Ernesto; Brogi, Antonio (Wiley, 2024)
The problem of managing multi-service applications on top of Cloud-Edge networks in a quality of service (QoS)-aware manner has been thoroughly studied in recent years from a decision-making perspective. However, only a few studies addressed the problem of actively enforcing such decisions while orchestrating multi-service applications and considering infrastructure and application variations. In this article, we propose a next-gen orchestrator prototype based on Docker to achieve the continuous and QoS-compliant management of multiservice applications on top of geographically distributed Cloud-Edge resources, in continuity with CI/CD pipelines and infrastructure monitoring tools. Finally, we assess our proposal over a geographically distributed testbed across Italy.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/7567#journalPolicy
Keywords: Informática - Aplicaciones; Application orchestration; Cloud-Edge continuum; Continuous management; Continuous reasoning; Multiservice application